Chapter La documentazione dell'archivio Cerrito per la storia sociale del Novecento - Dadà, Adriana (Strumenti per la didattica e la ricerca, 2021)
The contribution illustrates the figure of Gino Cerrito as a scholar and the importance of his archive for the social history of the twentieth century